Kings for three days : the play of race and gender in an Afro-Ecuadorian festival - Rahier, Jean Muteba, 1959- (Interpretations of culture in the new millennium., 2013)
With its rich mix of cultures, European influences, colonial tensions, and migration from bordering nations, Ecuador has long drawn the interest of ethnographers, historians, and political scientists. In this book, the author delivers a highly detailed, thought-provoking examination of the racial, sexual, and social complexities of Afro-Ecuadorian culture, as revealed through the annual Festival of the Kings.